Relevance and justification of the regional development agency approach for the Brcko district of BiH - Igor Pellicciari; Admir Nukovic (European Regional Science Association (ERSA), 2002)
Still facing the consequences of a post-war and a post-communist transition, BiH is trying to consolidate the strategies for a sustainable peace, based on institutionalisation of a pluralistic democracy - less obsessed by the ethnic questions - and a socio-economic development - that does not necessarily have to rely on the international assistance. Bosnia and Herzegovina is far from being an unitarian institutional, political and social subject and the differences that have marked the years of the war have got consolidated in a constitutional structure that is for sure one of the most complicated that are currently existing in the world. The lack of the presence of a State in the policy making process, is often filled up in Bosnia by the emerging role of local authorities. The case of Brcko District of Bosnia and Herzegovina is rather unique and is a sort of paradox in the paradox of the BiH situation. After getting an autonomous status which was a result of a long and tiring political mediation, Brcko District is now facing the challenge of building a regional development strategy, which has not only to be "politically correct" (like almost all the decisions that have been recently regarding this little but strategic territorial area, so crucial for the BiH peace stability) but has as well to match the difficulties of achieving a future sustainability. The following paper aims to give an answer to the following crucial questions: Does it make sense to promote a regional development strategy and the institutionalisation of a Development Agency for a limited territorial area like Brcko, created as a consequence of a war scenario? What is the specificity of Brcko and what -on the contrary- can be used to build up a model replicable elsewhere in BiH?
Keywords: 330